2016
DOI: 10.3402/fnr.v60.32783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stachyose on absorption and transportation of tea catechins in mice: possible role of Phase II metabolic enzymes and efflux transporters inhibition by stachyose

Abstract: BackgroundNutritional and absorption-promoting properties of stachyose combined with tea catechins (TC) have been revealed. However, the mechanism involved in non-digestible oligosaccharides-mediated enhancement of flavonoid absorption has largely remained elusive.MethodsThis study was designed to investigate the molecular mechanism of stachyose in enhancing absorption and transportation of TC in mice. Mice were orally pre-treated with stachyose (50, 250, and 500 mg/kg·bw) for 0–8 weeks, and 1 h before sacrifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We suppose that this may be related to the fact that stachyose promotes the absorption of tea polyphenols in mice Li, Lu, Huang, Han, & Yang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We suppose that this may be related to the fact that stachyose promotes the absorption of tea polyphenols in mice Li, Lu, Huang, Han, & Yang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the bioavailability of polyphenols depends on multi-drug resistance proteins on the cell membrane surface 45 and p-glycoproteins 46 . Recent studies involving human models considered the evidence on absorption, distribution, metabolism, and bioavailability.…”
Section: Bioavailability Of Polyphenolsmentioning
confidence: 99%
“…Nanostructure-based delivery systems are a topic of keen interest in increasing the plasma concentration of EGCG, with the attributes of enhancing the solubility of EGCG, preventing degradation in the intestinal environment, and elevating the permeation in the small intestine. 8 It has also been reported that specific combinations of food factors such as L-ascorbic acid and sucrose, 9 genistein, 10 piperine, 11 quercetin, 12 and stachyose 13 can improve the bioavailability of EGCG.…”
Section: ■ Introductionmentioning
confidence: 99%